Anxiety and foreign language learning for young adolescents - López Montero, Rosberly (2018)
This paper aims at analyzing the most common factors that produce anxiety in a group of young adolescents learning English as a foreign language as part of the outreach project “ED-2884” in the Pacific Regional Center of University of Costa Rica. In order to do this, a modification of the Foreign Language Classroom Anxiety Scale (FLCAS) by Horwitz et al. (1986) is used. The study indicates that language anxiety is provoked mostly by impromptu speaking and the pressure to obtain good grades; meanwhile, listening exams and mistake making do not seem to represent a problem to these learners.